CD73 expression is critical to therapeutic effects of human endometrial regenerative cells in inhibition of cardiac allograft rejection in mice. (30th October 2020) - Hu, Yonghao; Kong, Dejun; Qin, Yafei; Yu, Dingding; Jin, Wang; Li, Xiang; Zhao, Yiming; Wang, Hongda; Li, Guangming; Hao, Jingpeng; Zhang, Baoren; Pang, Zhaoyan; et al.
Abstract: The newly found mesenchymal-like endometrial regenerative cells (ERCs) have been proved to induce immune tolerance in cardiac allograft transplantation. However, the therapeutic mechanism is not clear. The present study was undertaken to investigate whether ecto-5′-nucleotidase (CD73) expression on ERCs is critical to cardiac allograft protection. C57BL/6 mouse recipients receiving BALB/c mouse cardiac allografts were treated with unmodified ERCs or anti-CD73 monoclonal antibodies (mAb) pretreated ERCs, respectively. It has been found that CD73 expression was critical to ERC-induced attenuation of graft pathology. The blockage of CD73 expression on ERCs was related to the percentage decline of tolerogenic dendritic cells (Tol-DCs), macrophages type 2 (M2), and regulatory T cells (Tregs). As compared with anti-CD73 mAb pretreated ERCs group, CD73 expressing ERCs significantly increased the level of anti-inflammatory cytokine IL-10 but decreased levels of pro-inflammatory cytokines including IFN-γ and TNF-α. In addition, CD73 expressing ERCs showed tissue protective function via the regulation of adenosine receptor expression which was related to the infiltration of CD4 + and CD8 + cells in the allografts. Furthermore, significant increase of A2B receptors in the cardiac allograft was also associated with CD73 expressing ERC-induced prolongation of cardiac allograft survival. Abstract : Ecto-5′-nucleotidase (CD73) expression is critical to therapeutic effects of human endometrial regenerative cells in inhibition of cardiac allograft rejection in mice. The CD73 expression on human endometrial regenerative cells mainly affects three aspects: immune cells, cytokines, and the tissue expression of adenosine receptors.